THE USE OF VISUAL AUDITORY KINESTHETIC (VAK) LEARNING STYLES TO INCREASE STUDENTS VOCABULARY - RAHMAH WAHDANIATI SUAIB (Didaktika : Jurnal Kependidikan, 2017)
The objectives of this research were: (1) To find out whether or not the Visual Auditory Kinesthetic learning stylesincreases the students vocabulary. (2) To find out whether or not the students are interested in studying English by using Visual Auditory Kinesthetic learning styles. This research employed quasi experimental design. This research used cluster random sampling technique. The research data were collected by using two kinds of instruments namely: writing test for the students vocabulary achievement and questionnaire for the students interest. The results of the research were: (1) the implementation of Visual Auditory Kinesthetic learning styles in teaching vocabulary improve the students achievement as there is a significant difference vocabulary mean score of the experimental group in posttest was significantly higher than the control group (82.40 58.80). (2) The students interest in Visual Auditory Kinesthetic learning styles was categorized as very high. It can be concluded that the Visual Auditory Kinesthetic learning styles in the teaching process is effective to be implemented in improving the students vocabulary achievement and the students have high interest toward Visual Auditory Kinesthetic learning styles in teaching English vocabulary.